2016
DOI: 10.1007/s40506-016-0090-8
|View full text |Cite
|
Sign up to set email alerts
|

Dilemmas and Pitfalls in Rubella Laboratory Diagnostics in Low Prevalence or Elimination Settings

Abstract: The changing epidemiology of rubella in populations with either low prevalence levels, or where rubella elimination has been achieved, has challenged laboratory diagnostics. This review will discuss the challenges in identification of acute rubella and outline appropriate confirmatory testing, particularly for cases with low pretest probability. Implementation of pre-analytical screening processes can mitigate follow-up testing required to confirm false positive antibody results, and laboratories should consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…RT-PCR can be used to detect measles in urine specimens up to several weeks after disease onset, providing a non-invasive specimen option, which can also be used for genotyping [ 33 ]. Avidity testing can provide important contextual information, since samples from recently infected individuals would have low IgG antibody avidity, while those from those infected or immunized in the past would have high IgG antibody avidity [ 16 ]. For measles, plaque reduction neutralization tests of high avidity sera can be used diagnostically, with high concentrations of neutralizing antibodies being indicative of true cases [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RT-PCR can be used to detect measles in urine specimens up to several weeks after disease onset, providing a non-invasive specimen option, which can also be used for genotyping [ 33 ]. Avidity testing can provide important contextual information, since samples from recently infected individuals would have low IgG antibody avidity, while those from those infected or immunized in the past would have high IgG antibody avidity [ 16 ]. For measles, plaque reduction neutralization tests of high avidity sera can be used diagnostically, with high concentrations of neutralizing antibodies being indicative of true cases [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) can be used for direct detection of virus, but may not be available in all settings [ 13 ]. Avidity testing and plaque reduction neutralization testing of high-avidity samples may provide important additional information and also be a means of diagnosis in low-burden settings [ 15 , 16 ]. Serological Immunoglobulin M (IgM) testing using either capture or indirect enzyme immunoassays [ 14 ] has been a standard laboratory method for diagnosis of acute measles and rubella infections, since it is more readily available than PCR, and faster and less technically challenging than viral culture [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…(P-value = 0.14). (which is low) is diagnosed as prenatal infection (8). The virus can be recovered from the posterior pharynx and conjunctiva, CSF, or urine.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, none of the methods for detecting anti-rubella IgM antibody evaluated in this study had the combination of high sensitivity and high specificity that is needed to support monitoring of elimination goals, although this could be somewhat compensated for by taking a presumptively positive approach to specimens with equivocal results (particularly Microimmune and Euroimmun glycoprotein methods). These underperforming methods, when combined with low rubella prevalence in elimination settings, lead to poor predictive ability and are therefore of limited value ( 5 , 6 , 21 23 ). A study conducted in the province of Ontario, Canada, a setting without endemic circulation of rubella, reported that the positive predictive value of a positive rubella IgM test for case confirmation was 3.6% ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, this was often achieved through detection of rubella specific IgM antibodies although it has been augmented or replaced by virus detection by RT-PCR, particularly in countries approaching or having achieved elimination (3)(4)(5)(6). Nonetheless, IgM serology remains an important tool in many countries where it can be used for case confirmation (endemic settings) and active disease surveillance (case finding in elimination settings) through reflex or co-testing of sera captured through other surveillance systems, such as measles and arboviruses (7,8).…”
Section: Introductionmentioning
confidence: 99%